Thyroid fine needle aspiration biopsy results before and during the COVID-19 pandemic: From a single-center perspective - Babayeva, Afruz; Coskun, Meric; Yalcin, Mehmet Muhittin; Uzun, Arzu; Inan, Mehmet Arda; Eroglu Altinova, Alev; Akturk, Mujde; Karakoc, Mehmet Ayhan; Balos Toruner, Fusun; Yetkin, Ilhan (Annals of Medical Research, 2023)
Aim: One of the effects of the COVID-19 pandemic on the healthcare system has been the postponement of elective procedures. We aimed to investigate how the COVID-19 pandemic has affected our thyroid fine-needle aspiration biopsy (FNAB) results. Materials and Methods: The distribution of cytology results during the 16.5 months of the pandemic was compared with the pre-pandemic period by The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) diagnostic categories. Results: The number of FNABs performed during the pandemic period decreased by 27.3% compared to the pre-pandemic period in our center, in line with the recommendations (1,197 to 327 diagnostic FNABs). Benign biopsy results decreased during the pandemic period compared to the pre-pandemic period (77.3% to 49.5%, p<0.001), and indeterminate biopsy results (AUS/FLUS, FN/SFN, and SUS) increased from 19.5% to 45.9 %, p<0.001. Malign biopsy rates did not differ between pre-pandemic and pandemic periods (3.3% to 4.6%, p=0.25). Conclusion: Although the number of FNAB decreased due to pandemic measures, we found a decrease in benign cytology and an increase in indeterminate for malignancy. The pandemic period allowed us to be more selective when deciding on a biopsy for FNABs. We recommend that the risk assessment of nodules be done carefully when making the biopsy decision in the next period. Although it is recommended not to delay FNAB for nodules at risk for malignancy, it should not be forgotten that the surgical decision should not be hasty in indeterminate results, and follow-up can be continued, or biopsy can be performed again under appropriate conditions.